The potential of ICT for the development and economic restructuring of the new EU member states and candidate countries - Marcin Piatkowski (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
The purpose of this paper is to analyze the potential of ICT in the Central and Eastern European (CEE) countries for faster convergence with the EU-15 income level. The paper investigates this question from both macro and industry perspectives. First, it argues that, between 1995 and 2001, ICT contributed to accelerated growth in all five new EU member states (a case of technological leapfrogging) and thus contributed to their faster convergence with the EU-15. However, in two of the EU candidate countries - Romania and, to a lesser extent, Bulgaria - the income gap widened, mainly due to the lower quality economic and institutional environment. Second, the paper shows that ICT use had an important role in stimulating productivity growth at industry level in the CEE countries. Third, it argues that ICT offers significant potential for faster productivity growth in today's non-ICT using industries. If these industries were able to achieve the same rate of productivity growth as the ICT-using industries, then they would make a significant contribution to faster growth in the CEE countries. Realizing this potential, however, will crucially depend on far-reaching structural reforms, business reorganization and investment in human capital. Finally, the paper develops a methodology, on the basis of which it speculates that some industries in CEE countries stand to benefit more from ICT use than others.
Keywords: 330; Informationstechnik; Wirtschaftliche Konvergenz; Osteuropa; EU-Staaten